0658 Phenotypic Characterization Of Rls In African-americans. (12th April 2019) - Saini, Prabhjyot; Forbes, Alison; Rye, David B
Abstract: Introduction: Knowledge of RLS diagnosis and treatments and its genetic architecture derive almost solely from populations of European background. Sparse knowledge of RLS phenotypes exists in other demographics.We characterize African Americans (AA) with RLS in a specialty clinic. Methods: Fifty-nine (nine men) patients identifying as AA (≥25% African heritage) where gold standard RLS affectation was determined by face-to-face clinical evaluations were recruited.Average age was 50.2 ± 15.1 and BMI (36.3 ±7.96; women). At time of evaluation, only one subject was being treated for RLS.Subjects completed a 29-item RLS phenotype questionnaire, the IRLSSG severity rating scale, and the Insomnia Severity Index (ISI) (N=26).More than 80% had undergone PSG or HST. Results: The 4 diagnostic criteria for RLS where symptom ≥ 2-4 days/month was met in 71.2%. Symptoms were daylong (39%), restricted to bedtime (27.1%), or also present before and/or after dinner (25.4%).The average IRLSSG severity scale score was 22.5 ± 6.8. Symptom onset was ≥ 30 yr old in 71.2%.25% reported a 1st degree relative with RLS symptoms.Nearly 1/2 (n=27) described their symptoms as painful. Symptoms interfered with falling (54.2%) and staying asleep (40.7%), and 44% met clinical criteria for insomnia (with ISI of 21.68 ± 6.8).The commonest self-reported comorbidities were HTN (55.93%), iron deficiency (50.9%), anemia (45.8%), and depression (35.6%). Women often reported current (N=11) or resolved (N=15) PICA. OSA was mild (41%), moderate (23%), or severe (20%). PLM index ≥ 5/hour was present in 66% of PSGs. Two in lab evening questions failed to suggest RLS symptoms in ≤ 12% of instances. Majorities did not consume alcohol (78.6%), exercise (55.4%), use OTC sleep-aids (80%), or appreciate RLS worsening with pregnancy (78%). 61.8% had previously mentioned symptoms to a doctor, with 2/3rds of these having sought treatment specifically for RLS, and 89.1% accepting of a prescription medicine. Conclusion: Despite similarities to RLS in Caucasians, untreated symptoms in AAs exhibit a somewhat less pronounced diurnal preference, and higher rates of pain, insomnia, and comorbid OSA and iron deficiency, that may account for phenotypic differences as well as underdiagnosis in AAs despite positive attitudes and advocation for treatment Support (If Any): Arthur L. Williams Jr. Foundation and grateful patients.